Osteocalcin is associated with testosterone in the general population and selected patients with bone disorders. (13th January 2013) - Hannemann, A.; Breer, S.; Wallaschofski, H.; Nauck, M.; Baumeister, S. E.; Barvencik, F.; Amling, M.; Schinke, T.; Haring, R.; Keller, J.
Summary Research in the last decade has revealed that bone is not only a target tissue for numerous circulating hormones but functions as an endocrine organ itself. As a recent study demonstrated a stimulatory effect of the osteoblast‐derived hormone osteocalcin (OCN) on testosterone production in mice, we investigated whether such an association can be replicated in humans. We used data from 1338 men (25–86 years) in the population‐based epidemiological Study of Health in Pomerania and from 110 male outpatients with bone disorders (18–85 years) for the study. We analysed cross‐sectional associations between OCN and total testosterone serum concentrations (TT), as well as associations between further markers of bone turnover [bone‐specific alkaline phosphatase (BAP), serum C‐terminal telopeptides of Type I collagen (CTX), urinary deoxypyridinoline] and TT using ordinary least square (OLS) regression models. Multivariable OLS models revealed a positive association between OCN and TT in the population‐based (β coefficients for a one standard deviation increase, 0.590; standard error (SE), 0.175; p‐value, <0.01) and patient‐based (β coefficient, 0.575; SE, 0.132; p‐value, <0.01) samples even after adjustment for age and body mass index (both samples), and time of blood sampling (population‐based sample only). Furthermore, we observed positive associations between BAP and TT (β coefficient, 0.403; SE, 0.170; p‐value, 0.02) as well as between CTX and TT (β coefficient, 0.733; SE, 0.172; p‐value, <0.01) in men from the general population. The present investigation shows that OCN is associated with TT in the general population and in patients with bone disorders, and may thus indicate general male health status. Additional longitudinal observational studies are warranted to confirm our findings and future experimental research is necessary to elucidate potential mechanisms underlying the observed associations.